Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis Wordwall Terhadap Hasil Belajar Matematika Siswa Kelas V SDN 2 Baadia - Rosalia, Rosalia; Rasmuin, Rasmuin; Jais, Ernawati (Jurnal Akademik Pendidikan Matematika, 2024)
The formulation of the problem in this study is, is there any significant influence of using Wordwall-based interactive learning media on the mathematics learning outcomes of fifth grade students at SD Negeri 2 Baadia. The objective of this research is to find of the effect of using Wordwall-based interactive learning media on the mathematics learning outcomes of fifth grade students at SD Negeri 2 Baadia. This is quantitative research by applying the quasi experimental Design method. The population in this study were all class V students of SD Negeri 2 Baadia in the academic year 2023/2024, even semester, consisting of 2 classes, and the samples were class VA and class VB, totaling 46 students using the purposive sampling technique. Data collection in this research used observation and tests. The data obtained were analyzed using the independent sample T-Test. Based on the research results, it was concluded that the calculated t value > t table at the 5% significance level was 2,405 > 2,015. Thus, the value > then Ho is rejected, and has a significance value (2-way) of 0,02 < 0,05. So, it can be concluded that there is an influence of the use of Wordwall-Based Interactive Learning Media on the mathematics learning outcomes of class V students at SD Negeri 2 Baadia.